2019
DOI: 10.1016/j.trci.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Moderate‐ to high‐intensity exercise does not modify cortical β‐amyloid in Alzheimer's disease

Abstract: Introduction Animal models of Alzheimer's disease show that exercise may modify β-amyloid (Aβ) deposition. We examined the effect of a 16-week exercise intervention on cortical Aβ in patients with mild-to-moderate Alzheimer's disease. Methods Thirty-six patients with Alzheimer's disease were randomized to either one hour of aerobic exercise three times weekly for 16 weeks or usual care. Pre and post intervention, 11Carbon-Pittsburgh compound B positron emission tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 87 publications
1
25
0
Order By: Relevance
“…However, small human intervention studies have examined the impact of exercise on amyloid with inconclusive results. At least three intervention studies have examined the impact of exercise on serum amyloid concentration, with none reporting reliable reductions in amyloid as a consequence of exercise [ 62 64 ]. The amyloid tracer we employed (18F-AV45) may lack sufficient sensitivity/specificity to index subtle changes in amyloid induced by exercise in cognitively normal older adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, small human intervention studies have examined the impact of exercise on amyloid with inconclusive results. At least three intervention studies have examined the impact of exercise on serum amyloid concentration, with none reporting reliable reductions in amyloid as a consequence of exercise [ 62 64 ]. The amyloid tracer we employed (18F-AV45) may lack sufficient sensitivity/specificity to index subtle changes in amyloid induced by exercise in cognitively normal older adults.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the microscopical signs of Aβ deposits were not detectable after physical activity. Although cortical accumulation of Aβ has not been altered in high-intensity training (Frederiksen et al, 2019), it has also been published that training and running have a protective effect in the hippocampus of mice in AD (Schimidt et al, 2019). Although physical activity generally decreases the amount of Aβ deposits or concentration in the blood and cerebrospinal fluid (Brown et al, 2019), no data are available to clarify the mechanism in the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found no effect on cortical A levels (evaluated using PET) when patients with mild to moderate AD (assessed according to the NINCDS-ADRDA Alzheimers Criteria and DSM-IV codes [ 93 ]) undertook a 16 week exercise intervention (moderate to high intensity aerobic exercise three times weekly for one hour). In this case, the lack of efficacy may be due to the short intervention period, and relatively late stage of AD progression [ 94 ]. While changes in AD pathology have been demonstrated in a number of studies, these do not always translate to improvements in cognitive function.…”
Section: Exercise and Ad Protectionmentioning
confidence: 99%